2004
DOI: 10.1126/science.1101072
|View full text |Cite
|
Sign up to set email alerts
|

Ice Flow Direction Change in Interior West Antarctica

Abstract: Upstream of Byrd Station (West Antarctica), ice-penetrating radar data reveal a distinctive fold structure within the ice, in which isochronous layers are unusually deep. The fold has an axis more than 50 kilometers long, which is aligned up to 45 degrees to the ice flow direction. Although explanations for the fold's formation under the present flow are problematic, it can be explained if flow was parallel to the fold axis approximately 1500 years ago. This flow change may be associated with ice stream altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 18 publications
1
44
1
4
Order By: Relevance
“…can be achieved through the comparison of present-day fl ow from global positioning system (GPS) or satellite data with paleo-fl ow orientations derived from structure tracking of englacial layer features. Studies of this kind have shown that Holocene deglaciation (Conway et al, 1999) forced signifi cant fl ow regime change in the WAIS interior, with rapid and abrupt changes in the confi guration and rate of inland ice stream fl ow in the Ross Sea sector (e.g., Conway et al, 2002;Siegert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…can be achieved through the comparison of present-day fl ow from global positioning system (GPS) or satellite data with paleo-fl ow orientations derived from structure tracking of englacial layer features. Studies of this kind have shown that Holocene deglaciation (Conway et al, 1999) forced signifi cant fl ow regime change in the WAIS interior, with rapid and abrupt changes in the confi guration and rate of inland ice stream fl ow in the Ross Sea sector (e.g., Conway et al, 2002;Siegert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Primary evidence includes: englacial layer geometry indicative of ground-line migration and non-steady flow patterns (Siegert et al 2013;Kingslake et al 2016); small length-scale englacial folding thought to represent ice-stream convergent flow where there is presently slow flow (Bingham et al 2007(Bingham et al , 2015; and surface flow structure in a presently slow-flowing region (Glasser et al 2015). Additionally, buried crevasses in Kamb Ice Stream and Siple Dome suggest a stagnation of ice streams (Retzlaff & Bentley 1993;Jacobel et al 2000), flow stripe variability observed on the Ross Ice Shelf supports cyclical ice streaming activity with a frequency of between 100 and 1000 years (Fahnestock et al 2000), and variations in englacial radar reflector geometry are thought to show flow reorganization (Ng & Conway 2004;Siegert et al 2004). Most evidence for flow reorganization exists near ice-sheet margins but reorganization may be expected along the full length of the ice flow path.…”
Section: Q13mentioning
confidence: 99%
“…Although thermoviscous fingering (Section 4.2) has been appealed to as an explanation for ice streams, some ice streams are known to flow almost entirely by basal sliding (Engelhardt & Kamb 1997), and this sliding motion can change direction and speed (Siegert et al 2004, Hulbe & Fahnestock 2007 or even cease altogether without the bed actually freezing (Retzlaff & Bentley 1993, Catania et al 2003, pointing to subglacial drainage as a crucial factor (Anandakrishnan & Alley 1997).…”
Section: Ice Streamsmentioning
confidence: 98%